One-Pot Synthesis of 3-(1,2,3,4-Tetrahydroisoquinolin-1-yl)-isoquinolin-1(2H)-ones by DEAD-Promoted Oxidative Ugi–Wittig Reaction Starting from Phosphonium Salt Precursors - Zhao, Long; Yang, Mao-Lin; Sun, Mei; Ding, Ming-Wu (Synlett, 2021)
A new one-pot synthesis of 3-(1,2,3,4-tetrahydroisoquinolin-1-yl)-isoquinolin-1(2H)-ones by DEAD-promoted oxidative Ugi–Wittig reaction was developed. The sequential reactions of (2-carboxybenzyl)triphenylphosphonium salts, isocyanides, and N-aryl-1,2,3,4-tetrahydroisoquinolines produced 3-(1,2,3,4-tetrahydroisoquinolin-1-yl)-isoquinolin-1(2H)-ones in moderate to good overall yields in the presence of DEAD and Et3N.
Keywords: isoquinolin-1(2H)-one; oxidative Ugi reaction; Wittig reaction; (2-carboxybenzyl)triphenylphosphonium salt; 1,2,3,4-tetrahydroisoquinoline